Pengaruh Kegiatan Outbond Terhadap Kecerdasan Kinestetik Pada Anak Kelompok B Di Tk PG Tasikmadu Tahun Ajaran 2015/2016 - Ibrahim, Helmi Malik; , Wili Astuti, S.Pd, M.Hum (2016)
The purpose of this study was conducted to determine the effect of the kinesthetic intelligence outbound activities for children in kindergarten groups PG Tasikmadu Academic Year 2015/2016. The method used in this research is quantitative method using a kind of experimental research with pre- design study experintal design is one group pretest-posttest design. This research was conducted in kindergarten PG Tasikmadu. Subjects who used as many as 21 children are in kindergarten children in group B Tasikmadu PG. Data collection techniques in this study using observation, that observation participate (participan observation). Data analysis techniques used in this study is ttest with the help of the program SPSS 16.0 for Windows. The results of the data analysis using ttest obtained thitung -10 944 -2.086 ≤ -ttabel then H0 and H0, which means there are significant outbound activity against kinesthetic intelligence in children.